Framing China-Malaysia trade relations beyond Asean: Factoring the regional comprehensive economic partnership - Devadason, E.S. (2014)
The paper frames the trade relationship between China and Malaysia within the context of ASEAN and the impending RCEP. Specifically trade potentials are derived for the bilateral partnership within the two structures to identify whether China's external options under the RCEP affect her relationship with Malaysia. Potentials for trade expansion between China and Malaysia, estimated through a three-dimensional panel gravity model, are found to be marginally lower under the RCEP structure relative to ASEAN. More importantly, trade potentials appear exhaustedfor major products traded under both contexts. This suggests a change (decline) in the trade posture of the China-Malaysia partnership as relative advantages are most likely to be altered under the expanded matrix of Chinese relations with RCEP members. In coping with the larger matrix structure, both nations should innovate new forms of bilateral cooperation, beyond trade, to enhance their strategic partnership.